Effects of Social Media Marketing and Brand Love-Jealousy on Willingness to Pay Premium - Farrastia Rana Ramadianti; Sarah Afifah Risani Hidayatullah; Shania Karla (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
In previous marketing academics, there is a recent increase found in adjusting and applying concepts of psychology and interpersonal theories to the brand management concept, such as brand love and jealousy, and its effect on customers’ willingness to pay a premium price. Social media marketing has also received a growing interest regarding its influence on customer-brand relationship. However, the number of related studies focusing on the dynamic Indonesian market is still very limited. The direct influence of SMM activity on brand love in the context of premium brands is also still underexplored. Our purpose in this research is to study the effect of Indonesian young adults’ self-esteem and brands’ social media marketing activities on creating individual’s brand jealousy. A quantitative approach based on questionnaire is used to test the conceptual model that describes the relationships between social media marketing, brand love, self-esteem, brand jealousy, and willingness to pay premium. The findings of this research show that social media marketing positively influences brand love, brand love also positively affects brand jealousy, and brand jealousy has a positive impact to willingness to pay premium. However, self-esteem does not seem to have a significant positive correlation with brand jealousy. The results also provide strategic insights for premium brand managers marketers to motivate customers to pay premium prices’s by focusing on innovative social media strategies and creative content development that appeals to customers' feelings and drive purchase decisions.